Black money and ways to combat its whitening: A comparative study - Tahseen, Muhammad (Journal of Legal Sciences, 2023)
The phenomenon of black money laundering (money laundering) receives wide and great attention from researchers of all their intellectual orientations, legal or economists, as this process acquires great importance in light of commercial developments and electronic transactions, Especially after the opening of Iraq to the outside world after 2003, and there are many factors that encourage the process of money laundering, including the large number of crimes, the prevalence of financial and administrative corruption, and the weakness of legal procedures to combat it, as the phenomenon of black money laundering is considered a criminal case that affects developed and developing countries. Because it impedes the tracking and seizure of funds of criminal origin, In addition to its role in spreading corruption and financing terrorism, and its impact on the justice apparatus, political and media institutions, in addition to its impact on other sectors of society, so this research aims to shed light on this phenomenon with its stages and methods, and the mechanism for combating it internationally and internally.